Longitudinal analysis of maternal serum Follistatin concentration in normal pregnancy and preeclampsia. (12th February 2015) - Garcés, María F.; Vallejo, Sergio A.; Sanchez, Elizabeth; Palomino‐Palomino, Miguel A.; Leal, Luis G.; Ángel‐Muller, Edith; Díaz‐Cruz, Luz A.; Ruíz‐Parra, Ariel Iván; González‐Clavijo, Angélica M.; Castaño, Justo P.; Abba, Martin; Lacunza, Ezequiel; et al.
Summary Objective Follistatin (FST) is a regulator of the biological activity of activin A (Act A), binding and blocking it, which could contribute to the modulation of its pro‐inflammatory activity during pregnancy. We sought to investigate, in this nested case–control study, FST serum levels during normal pregnancy and correlate it with the FST profile in preeclamptic pregnant women, normal pregnant women followed 3 months postpartum and eumenorrheic nonpregnant women throughout the menstrual cycle. Subjects and Methods Follistatin serum levels determined by ELISA, biochemical and anthropometric variables were measured in normal pregnant (n = 28) and preeclamptic (n = 20) women during three periods of gestation. In addition, FST serum levels were measured in a subset of normal pregnant women (n = 13) followed 3 months postpartum and in eumenorrheic nonpregnant women (n = 20) during the follicular and luteal phases of the menstrual cycle. Results Follistatin serum levels in the eumenorrheic nonpregnant and postpartum group were significantly lower when compared to levels throughout gestation (P < 0·01). Serum FST levels increased in each period of pregnancy analysed, being significantly higher towards the end of gestation (P < 0·01). FST levels were lower in late pregnancy in preeclamptic women compared to normal pregnant women (P < 0·05). Finally, FST levels were higher in the luteal phase when compared with the follicular phase of the menstrual cycle (P < 0·05). Conclusions These analyses would permit the consideration that changes in FST levels during pregnancy contribute to the control of the Act A system.